Development of Interactive Games in Plane Figure Materials With Ethnomathematics Approaches in Elementary School - Habsah, Ilvia; Putri, Linda; Jauharin Farda, Ummu; Sa'idah, Nusrotus (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The purpose of this research is to develop effective and innovative learning tools that can improve the understanding of mathematical concepts on the material of building space. This research is Research and Development by applying the Reiser and Molenda model. The final validation result of the product from the material expert is 89.4% while the media expert is 97%, so this media product is declared very feasible to use in the learning process. N-Gain was used to measure the improvement of learning outcomes. From the analysis results, the control group average was 52.3 and the experimental average was 55.90. This study also proved that there was a significant difference in the learning outcomes of the experimental group and the control group from the independent sample t-test of t = 3.74; p = 0.001; ES = 0.973. The importance of integrating innovative and contextual learning media offers educators guidance to design more engaging and effective learning strategies, as well as enriching students' learning experiences by utilizing cultural and technological elements in education.